Mengembangkan Usaha Mikro, Kecil Dan Menengah Dengan Melakukan Pembukuan Pencatatan Akuntasi Sederhana Di Kelurahan Mijen, Kecamatan Mijen, Kota Semarang - Camilus Isidorus; Suprantiningrum Suprantiningrum; Amsar Amsar; Sri Haryanti; Joko Riyanto; Siti Aminah; Janti Soegiastuti (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, small and medium enterprises (MSMEs) are one of the drivers of the economy and help Indonesia's national economic growth. It has a very important role for national and regional economic growth. However, there are still obstacles or problems faced by MSME players, in particular the limitations of preparing simple bookkeeping. This can make MSME players more creative and innovative. One thing MSME players can do is by carrying out simple accounting records. The aim of this service activity is that MSMEs can improve their understanding and accounting skills, improve the quality of financial records, make MSMEs independent and sustainable and increase access to capital. The method of this service is by providing education on simple accounting records. The service activities ran smoothly and the community was very enthusiastic about participating in the activities until the end. This activity can help improve Human Resources and contribute to local economic growth.